G.G. Belli's language trials, C.M. Maggi's pragmatism, Dante's linguistic theory (Atti del Sodalizio Glottologico Milanese, 2018)
Gioachino Belli’s “Introduction” to his poems offers an intriguing example how Dante’s linguistic approach to the poetical matter can affect a XIX century Italian poet. The relation between the “Introduction” and “De vulgari eloquentia” is here detected on the base of parallelisms within a shared interpretation of the sharp opposition affecting language skills acquired in a natural way or a language achievement assumed in the school environment. KEYWORDS: language variation within Italian; written and common language; poetical matters; natural linguistic skills; achievements of language levels